Redeeming Love - Rivers, Francine, 1947- ([Colorado Springs] : Multnomah, 2021)
Californias gold country, 1850. Angel expects nothing from men but betrayal. Sold into prostitution as a child, she survives by keeping her hatred alive. Then she meets Michael Hosea, a man who seeks his Fathers heart in everything. He obeys God;s call to marry Angel and to love her unconditionally. Defying Angels every bitter expectations, despite her resistance her frozen heart begins to thaw. But overcome by feelings of unworthiness and fear, Angel runs away from her husbands love. She is terrified of the truth she can no longer deny: Her final healing must come from the One who loves her even more than Michael Hosea does-- the One who will never let her go.
"This is the redeemed version of Redeeming love, published by Bantam Books in 1991. The original edition is no longer available"--Copyright page.
"Soon to be major motion picture"--Cover.
Keywords: Women pioneers -- Fiction; Frontier and pioneer life -- Fiction; Frontier and pioneer life -- California; San Francisco; Fiction; Conduct of life -- Fiction; Man-woman relationships -- Religious aspects; Christianity; Fiction; Marriage -- Fiction; Prostitutes -- Fiction; Ex-prostitutes -- Fiction; San Francisco (Calif.) -- Fiction; California -- History -- 1850-1950; Fiction; Religious fiction; Romance fiction; Historical fiction